2014
DOI: 10.1139/cjm-2013-0723
|View full text |Cite
|
Sign up to set email alerts
|

Legume seed exudates and Physcomitrella patens extracts influence swarming behavior in Rhizobium leguminosarum

Abstract: Plants are known to secrete chemical compounds that can change the behavior of rhizosphere-inhabiting bacteria. We investigated the effects of extracts from legume host plants on the swarming behavior of Rhizobium leguminosarum bv. viciae. We also investigated the effects on swarming when Rhizobium is exposed to extracts from an ancestor to vascular plants, the model bryophyte Physcomitrella patens. Lentil and faba bean seed exudates enhanced and inhibited swarming motility, respectively, whereas pea seed exud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The moss Physcomitrella patens ( P. patens ) produces chemical compounds that increase swarming of Rhizobium leguminosarum , which is a process of rapid and coordinated movement of bacteria leading to rhizosphere colonization (Tambalo et al, 2014). Movement is probably related to increased expression of genes involved in flagellar filament formation and motility.…”
Section: Interaction Of Basal Land Plants With Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…The moss Physcomitrella patens ( P. patens ) produces chemical compounds that increase swarming of Rhizobium leguminosarum , which is a process of rapid and coordinated movement of bacteria leading to rhizosphere colonization (Tambalo et al, 2014). Movement is probably related to increased expression of genes involved in flagellar filament formation and motility.…”
Section: Interaction Of Basal Land Plants With Microbesmentioning
confidence: 99%
“…Bacterial swarming behavior can be influenced by plant strigolactone, since extracts of a strigolactone-deficient moss mutant induce less swarming motility in R. leguminosarum . Accordingly, the existence of beneficial interactions between moss and rhizobia, suggest a potential ancient signal perception mechanism between these type of bacteria and plants (Tambalo et al, 2014). Studies of moss-associated bacteria in different ecosystems have shown the presence of diverse microbial populations with a high proportion of antagonistic isolates to fungal pathogens, suggesting that mosses harbor bacteria with antifungal activities that contribute to plant defense (Opelt et al, 2007a,b).…”
Section: Interaction Of Basal Land Plants With Microbesmentioning
confidence: 99%
“…To identify possible cues, we tested the following: (i) sibling seed þ DW (control), (ii) non-sibling seed þ 100 ). Each 124 extract was derived from a single seed with no visible cracks (a commonly used approach to collect of seed extract [19,20]). If discrimination of the presence of seeds of another species depends on water-soluble chemicals, then seeds in ST5 will germinate faster than those in the sibling condition and faster than or in synchrony with those in the NST5 condition.…”
Section: (F ) Extract Experimentsmentioning
confidence: 99%
“…However, the crystal structure of the rice strigolactone receptor D14 resembles that of the Bacillus subtilis RsbQ protein that is a stress-response regulator with hydrolase activity (Kagiyama et al 2013), indicating that strigolactones might influence rhizobial cellular activity in a manner different from that tested above. Indeed, a role for strigolactones has been implied in the chemical dialog between plants and rhizobia (Peláez-Vico et al 2016;Tambalo et al 2014). For instance, extracts of the moss Physcomitrella patens stimulate the swarming motility, i.e., a rapid coordinated movement of bacteria across a surface, in Rhizobium leguminosarum, whereas this promoting effect is reduced by extracts from the strigolactone-deficient strain Physcomitrella patens Ppccd8D (Peláez-Vico et al 2016;Tambalo et al 2014).…”
mentioning
confidence: 99%
“…Indeed, a role for strigolactones has been implied in the chemical dialog between plants and rhizobia (Peláez-Vico et al 2016;Tambalo et al 2014). For instance, extracts of the moss Physcomitrella patens stimulate the swarming motility, i.e., a rapid coordinated movement of bacteria across a surface, in Rhizobium leguminosarum, whereas this promoting effect is reduced by extracts from the strigolactone-deficient strain Physcomitrella patens Ppccd8D (Peláez-Vico et al 2016;Tambalo et al 2014). In addition, rac-GR24 triggers the swarming motility of Sinorhizobium meliloti in a dose-dependent manner (Peláez-Vico et al 2016).…”
mentioning
confidence: 99%